Genetic Contribution to Variation in Blood Calcium, Phosphorus, and Alkaline Phosphatase Activity in Pigs - Reyer, Henry; Oster, Michael; Wittenburg, Dörte; Murani, Eduard; Ponsuksili, Siriluck; Wimmers, Klaus (Frontiers in Genetics, 2019)
Blood values of calcium (Ca), inorganic phosphorus (IP) and alkaline phosphatase activity (ALP) are valuable indicators for mineral status and bone mineralization. The mineral homeostasis is maintained by absorption, retention and excretion processes employing a number of known and unknown sensing and regulating factors with implications on immunity. Due to the high inter-individual variation of Ca and P levels in the blood of pigs and to clarify molecular contributions to this variation, the genetics of hematological traits related to the Ca and P balance were investigated in a German Landrace population, integrating both single-locus and multi-locus genome-wide association study (GWAS) approaches. Heritability estimates suggest a moderate genetic contribution to Ca, IP, ALP and the Ca/P ratio (0.27-0.54), with values for IP and ALP almost twice as high as the others. The genome-wide analysis of markers adds a number of genomic regions to the list of quantitative trait loci, some of which overlap with previous results. Despite the gaps in knowledge of genes involved in Ca and P metabolism, positional candidate genes like THBS2, SHH, PTPRT, PTGS1 and FRAS1 with reported connections to bone metabolism were derived from the significantly associated genomic regions. Additionally, genomic regions harbored functional candidates such as TRAFD1 and genes coding for phosphate transporters (SLC17A1-A4), which deserve further analysis. The study calls for improved functional annotation of the proposed candidate genes to derive features involved in maintaining Ca and P balance. This gene information can be exploited to diagnose and predict bone development and a well-functioning musculoskeletal system in pig husbandry and breeding.